Knowledge, Attitudes and Practices Related to Breast Cancer Screening Among Female Doctors of a Tertiary Care Hospital in Bangladesh (Journal of Chittagong Medical College Teachers' Association, 2020)
Background: Doctors with inadequate knowledge and unfavorable practice in their own life will be sub-optimal in their performance in community. This study aimed to determine the Knowledge, Attitudeand Practice (KAP) regarding Brest Self Examination (BSE) Clinical Breast Examination (CBE) and mammographyas screening test for breast carcinoma among female doctors.Materials and methods: This cross-sectional study was conducted on working female doctors of Chittagong Medical College Hospital, a tertiary care hospital of Bangladesh. A semi-structured self-administered questionnaire was used for data collection which was consisted of four parts: i) Demographic characteristics ii) KAP about BSE iii) KAP about CBE iv) KAP about mammography. A total of 100 forms were distributed and 84 were returned back.Results: The mean (SD) age of the female doctors was 38.92 ±7.52 (Range, 27-59 years).Family history of Breast cancer was positive in 15.5% and 96.4% of the doctors were married, Out of those with positive family history, 4 (30.76%) were 1st degree relatives of the respondents. Regarding to their knowledge proportion of doctors had heard about BSE, CBE and mammography were 100%, 97.6% and 100% respectively. But proportion of doctors did not know the exact starting age for BSE and mammography were 61.9% and 11.9% respectively. Moreover, 13.1% didn’t know who should do the BSE, 11.9% reported that, trained nurse should do CBE, about 41% reported that CBE should be done by either mammography or ultrasonography. Regarding attitude majority considered BSE (100%), CBE (96.4%) and mammography (91.7%) as useful tool for early detection of breast cancer. Out of 36 doctors age 40 years 23.8% never practiced BSE and only 11.1% done mammography for themselves.Conclusion: Though doctors had positive attitude towards BSE, CBE and mammography as screening tests their knowledge and practices regarding these test were not optimal. Emphasis should be laid on BSE and CBE in undergraduate and postgraduate courses for doctors.JCMCTA 2020 ; 31 (1) : 48-53